Peningkatan Keterampilan Berbicara Bahasa Inggris Melalui Model Pembelajaran Proyek - Putri, Mercy Krisita Omega; Korompot, Chairil Anwar; Kaharuddin, Andi Lidiyawati (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. This classroom action research is entitled Improving English-Speaking Skills through a Project Learning Model. This study aims to improve the English-speaking skills of students through a project learning model. Data collection was carried out through observation and questionnaire. This research was conducted in three meetings. Based on the results of observation and questionnaire at the first meeting, students stated that they had difficulty speaking English due to lack of confidence and lack of vocabulary. At the second meeting, the value of students' speaking skills reached 54%. Of the 37 students, there were 20 students who had achieved a minimum standard of completeness score of 75 or over 75. At the third meeting, the average of students’ activity increased significantly to 89%. There were 33 students out of 37 students who had achieved a standard of minimum completeness score of 75 or over 75. Based on the findings of this Classroom Action Research it can be concluded that through the project learning model, it is proven to be able to improve the students’ speaking skills Keywords: Speaking Skill, Learning Model, Project